2021
DOI: 10.3390/w13152032
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and Performance Analyses of the Distributed Hydrology–Soil–Vegetation Model Using Geomorphons for Landform Mapping

Abstract: Landform classification is important for representing soil physical properties varying continuously across the landscape and for understanding many hydrological processes in watersheds. Considering it, this study aims to use a geomorphology map (Geomorphons) as an input to a physically based hydrological model (Distributed Hydrology Soil Vegetation Model (DHSVM)) in a mountainous headwater watershed. A sensitivity analysis of five soil parameters was evaluated for streamflow simulation in each Geomorphons feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Geomorphon analysis [32], a technique that we employ in this research, is a machine vision terrain classifier of rasterized terrain models. Geomorphons have been often used to represent and even predict geomorphological and hydrological changes in river valleys [33][34][35][36]. In the form of input to a physically based hydrological model, geomorphons were successfully represented in the spatially distributed hydrological parameters of the upper reaches of a montane watershed in Brazil [33].…”
Section: Core Of Cranberry Gladesmentioning
confidence: 99%
See 1 more Smart Citation
“…Geomorphon analysis [32], a technique that we employ in this research, is a machine vision terrain classifier of rasterized terrain models. Geomorphons have been often used to represent and even predict geomorphological and hydrological changes in river valleys [33][34][35][36]. In the form of input to a physically based hydrological model, geomorphons were successfully represented in the spatially distributed hydrological parameters of the upper reaches of a montane watershed in Brazil [33].…”
Section: Core Of Cranberry Gladesmentioning
confidence: 99%
“…Geomorphons have been often used to represent and even predict geomorphological and hydrological changes in river valleys [33][34][35][36]. In the form of input to a physically based hydrological model, geomorphons were successfully represented in the spatially distributed hydrological parameters of the upper reaches of a montane watershed in Brazil [33]. Yan et al (2020) found geomorphons to be optimal in the characterization of subaqueous riverbed features on the Yangtze River, China [35]; while the work of Gioia et al (2021) showed geomorphon-based classification to be a robust tool for the identification of geomorphological landscape elements at a large scale in southern Italy [37].…”
Section: Core Of Cranberry Gladesmentioning
confidence: 99%